Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1111/j.1545-5300.1983.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Treatment of an Obsessive‐Compulsive Child: A Case Report

Abstract: This paper presents a family therapy approach to the treatment of an obsessive-compulsive child. Psychodynamic, behavioral and family therapy approaches to the etiology and treatment of this dysfunction are described briefly, and a detailed case report of a 15-session treatment utilizing behavioral interventions designed to change the family context is presented. Various procedures for dealing with the obsessive-compulsive behavior have been reported in the literature, including eliminating it directly by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Case studies showed advantages to parental involvement in treatment for children and young adults. [37][38][39] In a controlled study with a small sample, Emmelkamp and DeLange 40 compared the outcome of Dutch clients treated behaviorally with or without the spouse as cotherapist. Unfortunately, the content of psycho-educational interventions aimed at reducing conflict or enhancing communication was not described.…”
Section: Family Treatment Interventionsmentioning
confidence: 99%
“…Case studies showed advantages to parental involvement in treatment for children and young adults. [37][38][39] In a controlled study with a small sample, Emmelkamp and DeLange 40 compared the outcome of Dutch clients treated behaviorally with or without the spouse as cotherapist. Unfortunately, the content of psycho-educational interventions aimed at reducing conflict or enhancing communication was not described.…”
Section: Family Treatment Interventionsmentioning
confidence: 99%
“…Case studies showed advantages to parental involvement in treatment for children and young adults. [37][38][39] In a controlled study with a small sample, Emmelkamp and DeLange 40 compared the outcome of Dutch clients treated behaviorally with or without the spouse as cotherapist. Unfortunately, the content of psycho-educational interventions aimed at reducing conflict or enhancing communication was not described.…”
Section: Family Treatment Interventionsmentioning
confidence: 99%
“…Amanat, 1979;Bergman, 1980Bergman, ,1982Goldstein, 1973;Kolko & Milan, 1983;Wathney, 1982). The concept has also been applied to young children, either directly or by implication (Dalton, 1983;Erickson, 1962;Haley, 1973;Hare-Mustin, 1975: Madanes, 1980Zarske, 1982).…”
Section: Resistancementioning
confidence: 99%